Ukrainian national oppression during the russification of language and cultural space of the USSR: the 60's - 70's of the XXth century - Nadia Kindrachuk (Cхід, 2016)
In the article the author studied the russification and ideological language and cultural space of the Ukrainians during the 60's - 70's of the XXth century, showed the displacement of Ukrainian by widespread introduction of Russian, highlighted public policy of the totalitarian communist regime aiming to eliminate national differences, to move towards the nations, to achieve their full unity and creation of an "indivisible soviet people". The soviet authorities directed all efforts to strengthenRussia's national political advantage inUkraineand the implementation of the thesis of the Russian language as a "second mother" and thereby destroying the natural human sense of belonging to the Ukrainian nation. Those who spoke only Ukrainian, attracted the attention of the respective services, which could cast doubt on their political loyalty and cultivate an inferiority complex. Gradually, the ruling communist party elite considerably narrowed the scope of the Ukrainian language and formed the status of its inferiority. Abruptly decreasing percentage of the Ukrainian printed word, the Ukrainian theater lost its national face, the Russian language filled the radio and television. However, Ukrainian educators, writers, literary critics, filmmakers, painters, scientists and public figures stood actively against the process of russification ofUkraine's population and the "theory of bilingualism". The result of the confrontation between the national conscious Ukrainian intelligentsia and the Soviet bureaucracy was the appearance of the sixtiers, which eventually led the national revival of the late 1980's - early 1990's.